2012
DOI: 10.1021/jp212489k
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Studies on Selective Oxidation of Aromatic Ketone by Performic Acid

Abstract: The Baeyer-Villiger (B-V) reactions of 3,4-dimethoxy acetophenone (DMOAP), 4-methyl acetophenone (MAP), and acetophenone (AP) with performic acid (PFA) in formic acid (FA) solvent have been studied by density functional theory (DFT) method. The noncatalyzed and the formic acid-catalyzed reaction paths have been calculated at the MPWB1K/6-311++G(d,p)-IEF-PCM// MPWB1K/6-311G(d,p) level of theory. On the basis of the calculations, the attack of peracid to the carbonyl carbon is rate-determining in both the noncat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
(41 reference statements)
1
8
1
Order By: Relevance
“…In addition, our calculations showed that migration continued to be the RDS as solvent polarity increased. Some years ago, Liu and colaborators 29 performed a theoretical and experimental study of the BV reactions of acetophenone, 4-methylacetophenone, and 3,4-dimethoxyacetophenone, with PFA in FA acting both as catalyst and solvent. The authors claim that, according to their results, the addition step is the RDS for the three aromatic ketones.…”
Section: Introductioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In addition, our calculations showed that migration continued to be the RDS as solvent polarity increased. Some years ago, Liu and colaborators 29 performed a theoretical and experimental study of the BV reactions of acetophenone, 4-methylacetophenone, and 3,4-dimethoxyacetophenone, with PFA in FA acting both as catalyst and solvent. The authors claim that, according to their results, the addition step is the RDS for the three aromatic ketones.…”
Section: Introductioncontrasting
confidence: 99%
“…The energy data were refined by single-point calculations with the same functional and the 6-311++G­(d,p) basis set, with inclusion of the IEF-PCM continuum model using FA as solvent and the UFF radii. In our preceding studies, this functional was demonstrated to give excellent results that agree very well with previous experimental values. The thermodynamic magnitudes were obtained by vibrational calculation. The Gibbs energies were obtained via a thermodynamic cycle using corrections to Gibbs energies in the gas phase at 298.15 K using standard state 1 M and corrected electronic energies in solution.…”
Section: Computational Detailssupporting
confidence: 73%
See 3 more Smart Citations